2020
DOI: 10.3390/ijms21093111
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Disease and Tear Cytokine Levels—A Meta-Analysis

Abstract: Background—It is recognized that inflammation is an underlying cause of dry eye disease (DED), with cytokine release involved. We systematically reviewed literature with meta-analyses to quantitatively summarize the levels of tear cytokines in DED. Methods—The PubMed, Embase, Web of Science, Ovid, Cochrane, and Scopus databases were reviewed until September 2019, and original articles investigating tear cytokines in DED patients were included. Differences of cytokines levels of DED patients and controls were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 30 publications
2
53
2
3
Order By: Relevance
“…Abnormal increased inflammatory factors, including 1β, IL-6, IL-8, IL-10, interferon-γ, IFN-γ, and tumor necrosis factor-α, however, evidence was less strong for IL-2 and IL-17A. 25 While it was found that Th17 was a key immune cell that demonstrated main role in chronic ocular surface disorders. 26 The IL-17 cytokine family was named CTLA8 when it was discovered in 1993.…”
Section: Discussionmentioning
confidence: 98%
“…Abnormal increased inflammatory factors, including 1β, IL-6, IL-8, IL-10, interferon-γ, IFN-γ, and tumor necrosis factor-α, however, evidence was less strong for IL-2 and IL-17A. 25 While it was found that Th17 was a key immune cell that demonstrated main role in chronic ocular surface disorders. 26 The IL-17 cytokine family was named CTLA8 when it was discovered in 1993.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, previous studies have reported a significant correlation between low levels of tear lactoferrin and the development of both dry eye disease (DED) and chronic meibomitis [ 18 , 19 , 20 ] ( Figure 2 A). These two common disorders of the ocular surface system share a degree of mutual pathophysiology, since markers of inflammation and oxidative stress are present in both conditions [ 21 ]. Indeed, a decreased volume and an altered qualitative composition of tear film, together with excessive tear evaporation, lead to the creation of a hyperosmolar environment, which then initiates both inflammatory and oxidative cascades, resulting in impaired epithelial proliferation and differentiation [ 22 ].…”
Section: Lactoferrin and Dry Eyementioning
confidence: 99%
“…Indeed, zileuton produced additional, more specific anti-inflammatory effects. The first specific effect was the pronounced upregulation of IL-10, the anti-inflammatory cytokine previously found to be associated with DES [68]. Interestingly, a similar effect of zileuton against IL-10 was demonstrated in other inflammation-related disorders [69].…”
Section: Discussionmentioning
confidence: 66%